A peculiar case of dural venous sinuses with resulting atypical bony markings in posterior cranial fossa - Khorwal, Gitanjali; Kalra, Sunita (International Journal of Research in Medical Sciences, 2017)
A paramedian or midline suboccipital approach for craniotomies and craniectomies is commonly employed for decompression or tumour resections from posterior cranial fossa. The reference for midline is taken as the line joining the nasion and inion on the surface of the skull which is the estimated position of superior sagittal sinus. In the interior, the internal occipital protuberance is the site of confluence of sinuses which presents a spectrum of variations. An unusual pattern of drainage of dural venous sinuses was observed at the site of customary confluence during routine dissection of head region for undergraduate medical students in a sixty-year-old female cadaver. The superior sagittal sinus continued as right transverse sinus as usual but it was connected to the left transverse sinus through a venous channel. There was no appreciable confluence of sinuses at this site. A prominent and atypical cerebellar process emerged from right hemisphere of cerebellum and projected between right transverse sinus and the venous channel connecting right and left transverse sinuses. In the posterior cranial fossa, the internal occipital crest was present on the left of midline separated from internal occipital protuberance. Another small ridge was present to the right of midline. A triangular fossa thus formed on the right side of internal occipital crest was occupied by the unusual prominent process emerging from the right hemisphere of cerebellum.Pre-operative assessment of dural venous sinuses is imperative before any surgical intervention especially around the confluence of the sinuses.